The Associated Factors of Domestic Violence against Infertile Women - Fatemeh Alijani; Ahmad Khosravi; Mahdieh Sadat Mousavi; Vanessa Delarosa (Golestan University of Medical Sciences, 2019)
Background: Domestic violence (DV) against women is a global public health concern. The study was conducted to determine the associated factors of domestic violence against infertile women. Methods: This cross-sectional study was done on 379 infertile women referred to the infertility clinic in Sari, between October 2015 and March 2016. The convenience sampling was used considering inclusion criteria. Data was collected using Revised Conflict Tactics Scale (CTS2). Data was presented with descriptive statistics and Logistic regression to determine associated factors with DV in SPSS-16 software. The significant level was considered P<0.05. Results: Finding showed that majority of infertile women (88.9%) experienced domestic violence. The age (OR=0.91 95% CI: 0.85-0.99) and smoking (OR=8.12 95% CI: 1.87-35.21) with domestic violence. Conclusions: Regarding the high prevalence of domestic violence and its consequence on society, screening violence in health centers and support at-risk family via counseling are recommended.